Peroneal Nerve Injury due to Hip Surgery Located at the Knee Level: A Case Report - Mićić, Aleksa; Radojević, Stefan; Rasulić, Lukas (International Journal of Medical Students, 2023)
Background: A common peroneal nerve (CPN) injury located at the knee level, occurring as a consequence of hip surgery is described in the literature. However, there are only a few papers focusing on their surgical management, while there are no thoroughly analyzed cases following open reduction and internal fixation (ORIF) of the acetabular fracture. This paper aimed to describe such a case and discuss current trends in the surgical management of these patients. Case: A 32-year-old woman was admitted to our department due to left-sided CPN palsy. The patient was injured in a traffic accident eight months earlier, followed by left hip dislocation and acetabular fracture. Following the acetabular fracture ORIF, a CPN palsy developed. The electromyoneurography (EMNG) and ultrasound (US) indicated a nerve lesion at the knee level. The surgical treatment included external neurolysis, decompression, and complete nerve deliberation, with the preservation of all nerve branches. The patient reported immediate relief and completely recovered 8 months following the surgery (Medical Research Council (MRC) grade = 5, Visual Analogous Scale (VAS) = 0). Conclusion: The cause of CPN palsy following hip surgery may not always be located in the hip region. A detailed anamnesis, physical examination, and diagnostic evaluation are necessary for the proper surgical management of these patients. In addition to the EMNG, the US should be essential in preoperative planning and choosing the most effective surgical strategy.